(untitled) (Edad Media. Revista de Historia, 2026)
This article examines female ownership of local churches and monasteries in the Kingdom of León between the tenth and twelfth centuries, with the aim of understanding the role played by women from local communities and elites in managing these key spaces in the articulation of micropolitics. Drawing on a qualitative analysis of documentary evidence, it explores the mechanisms through which women gained control of these centres within the frameworks of kinship networks and local groups. The article concludes that, far from being passive figures, women exercised agency and utilized these spaces as platforms for power and social mediation, both within their communities and in relation to supralocal authorities.